Micro-planning for immunization in Kaduna State, Nigeria: Lessons learnt, 2017. Issue 48 (19th November 2018) - Umeh, Gregory C.; Madubu, Dauda M.; Korir, Charles; Loveday, Nkwogu; Ishaku, Sambo; Iyal, Hadiza; Omoleke, Semeeh A.; I Nomhwange, Terna; Aliyu, Atiku; Musa, Audu; Dankoli, Raymond; MI. Ningi, Adamu; et al.
Abstract: Background: The OPV 3 coverage for Kaduna State, 12–23 months old children was 34.4%. The low OPV 3 coverage, due mainly to weak demand for routine antigens and the need to rapidly boost population immunity against the disabling Wild Polio Virus (WPV), led the Global Polio Eradication Initiatives (GPEI) to increase supplemental OPV campaigns in Kaduna State, despite the huge cost and great burden on personnel. The OPV campaigns, especially in high risk (low vaccine uptake, <80% OPV 3 coverage and high vaccines refusal rate) states of northern Nigeria with poliovirus transmission has resulted in overestimated denominators or target population, as the highest ever vaccinated is used to set OPV campaign targets. Methods: We utilized a cross-sectional study that assessed the impacts and possible solutions to the challenges of overestimated denominators in immunization services planning, delivery and performance evaluation in Kaduna State, Nigeria. We used both descriptive and quantitative approaches. We enumerated households and obtained the target populations for routine immunization (<1 year), polio campaign (<5 years) and acute flaccid paralysis surveillance (<15 years). Results: We found a significant difference in mean scores between the micro-planning and supplemental vaccination data on a number of <5 years (M = 102967, SD = 62405, micro-planning compared to M = 157716, SD = 72212, supplemental vaccination, p < 0.05). We also found a significant difference in mean scores between the micro-planning and projected census data on a number of <1 year (M = 26128, SD = 16828, micro-planning compared to M = 14154, SD = 4894, census, p < 0.05). Conclusion: Periodic household-based micro-planning, aided with the use of technology for validation remains a useful tool in addressing gaps in immunization planning, delivery and performance evaluation in developing countries, such as Nigeria with overestimated denominators.